LOCALIZATION OF ACCESSORY PATHWAYS IN WOLFF PARKINSON WHITE SYNDROME USING R/S RATIOS ON SURFACE ECGs - Jamal, Syed Zahid; Zaidi, Kashaf Aqeel; Sheikh, Sajid Ali; Ahmed, Ammar; Irfan, Ghazala; Qadir, Faisal (Journal of Ayub Medical College Abbottabad, 2019)
Background: This study was conducted to establish the accuracy of R/S ratios in localizing accessory pathways in Wolff Parkinson White Syndrome on surface ECGs. Methods: This was a retrospective cross-sectional study from January 2002 till December 2016 conducted at National Institute of Cardiovascular diseases in Karachi, Pakistan. The sample included 157 patients with manifesting Wolff Parkinson White (WPW) Syndrome on a 12-lead surface ECG. As per the inclusion criteria, patients who had persistent or intermittent pre-excitation on surface ECG and had undergone electrophysiological study (EP) were included in the sample. Individuals with both successful and unsuccessful ablation procedures were included. Results: The sample consisted of 62.4% males (n=98) and 37.6% females (n=59) with mean age being 35.36±12.44. Accessory pathways (APs) were identified on the left side in majority of the patients with 54.1% (n=85) while right sided pathways were seen in 42.1% (n=66). Moreover, the most common accessory pathway amongst the males was Left Anterior (LA) and Left Lateral (LL) with a percentage of 48%, followed by Right Posteroseptal (RPS) at 20.4%. As opposed to this, the most common pathways amongst the females turned out to be RPS at 33.9% followed by LL and LA at 32.2%. Furthermore, the test using ratios were most effective in identifying left sided APs with sensitivity 74.1% and was least sensitive in identifying right sided pathways (sensitivity=40.7%). However, it was highly specific in locating right sided pathways with specificity of 94.6% as opposed to 83.3% in the left side. Furthermore, mid-septum regions had a sensitivity and specificity of 66.7% and 69.6% respectively. Conclusion: This establishes the effectiveness of R/S ratios in determining the location of accessory pathway based on the surface ECG prior to the ablation procedure. Since the younger population is affected more commonly, prolonged exposure to ionizing radiation can cause long term complications therefore, by this means, the duration of exposure can be reduced. Keywords: Wolff Parkinson White Syndrome; accessory pathways; surface ECG; electrophysiology ablation